Sending electronic direct mail as a facilitating condition for consumption: a theoretical-empirical study - Lacerda, Tales Sarmento; Veiga, Ricardo Teixeira (Revista Gestão da Produção Operações e Sistemas, 2008)
Some widely used action theories, like Theory of Planned Behavior (TPB), try to explain and predict consumer behavior from behavioral intentions. However, there are cases where intentions explain only a small part of behavior, making it necessary to study other variables in order to improve these models capacity for explanation. The Triandis model, introduced in 1979, suggests that the presence of facilitating conditions, together with intention and habit, can explain and predict behavior. This work studies the impact of sending electronic mail to consumers of a virtual video rental store as a facilitating condition, according to the Triandis Model. Using the companys electronic database, it can be observed that the use of this tool causes an increase in rental rates compared to previous consumer behavior. Keywords: Electronic mailing; Consumer Behavior, Facilitating conditions